Would you rather be a 'birth' or a 'genetic' mother? If so, how much? - Thornton, J G (1994)
Judges face difficult choices when the birth and genetic mothers of a child are separate people who dispute maternal access; the views of the general population may help them. Fifty women were asked whether, if they were infertile and could have only one child, they would prefer to be birth mothers (to carry a baby which was not genetically theirs) or genetic mothers (to have another woman carry their genetic baby). Similarly, fifty men were asked about their preference for a partner's child. In both groups the strength of preferences was measured using a lottery technique. The direction and strength of preferences was similar between men and women, and approximately equally divided between birth and genetic motherhood. These attitudes should be taken into account by those adjudicating custody disputes between such mothers.